2011
DOI: 10.3390/s110302525
|View full text |Cite
|
Sign up to set email alerts
|

Non-Destructive Techniques Based on Eddy Current Testing

Abstract: Non-destructive techniques are used widely in the metal industry in order to control the quality of materials. Eddy current testing is one of the most extensively used non-destructive techniques for inspecting electrically conductive materials at very high speeds that does not require any contact between the test piece and the sensor. This paper includes an overview of the fundamentals and main variables of eddy current testing. It also describes the state-of-the-art sensors and modern techniques such as multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
446
0
15

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 869 publications
(461 citation statements)
references
References 73 publications
0
446
0
15
Order By: Relevance
“…8 (a) and Fig.9 that the S21 values along the specimen edge are higher than those inside the flange area. This unexpected phenomenon is similar to the edge effect in the Eddy current technique, where the induced currents are distorted near the free edge [27]. Nevertheless, in the present case, the dent-peak in the image is still distinct from edge-peaks for recognition by an experienced operator, as the dent is located a sufficient distance from the edge.…”
Section: Magnitude and Phase Profilingmentioning
confidence: 59%
“…8 (a) and Fig.9 that the S21 values along the specimen edge are higher than those inside the flange area. This unexpected phenomenon is similar to the edge effect in the Eddy current technique, where the induced currents are distorted near the free edge [27]. Nevertheless, in the present case, the dent-peak in the image is still distinct from edge-peaks for recognition by an experienced operator, as the dent is located a sufficient distance from the edge.…”
Section: Magnitude and Phase Profilingmentioning
confidence: 59%
“…Eddy current instrumentation utilizes an alternating current electric coil-generated magnetic field to induce eddy currents in the component being examined. Typical electromagnetic field (EMF) penetration frequencies in eddy current testing range from 100 Hz to 10 MHz (Ansley et al, 1992;García-Martín, Gómez-Gil, & Vázquez-Sánchez, 2011), although García-Martín et al reported inspection frequencies of up to 25 MHz. Lippert et al (2007) found that workers at a turbine engine overhaul and repair center had recorded electromagnetic flux densities as high as 29.27 mT while carrying out magnetic particle inspection using a 3-phase 1400-5000 A 60 Hz alternating current system.…”
Section: Hazardsmentioning
confidence: 99%
“…Detection and characterization of a crack in a plate at its initial stage (before propagation), is a real industrial challenge and a major element in safety especially in high-risk areas. It is on the basis of these characterizations that engineers have the means to analyze such crack behavior, predict its spread and eventually assess its harmfulness as well as the life of the inspected body, [6]. In this paper, a numerical model for the assessment of eddy currents in materials, for the detection and characterization of defects is considered.…”
Section: Introductionmentioning
confidence: 99%